Circular Economy: Obtaining and Encapsulating Polyphenolic Compounds from Agroindustrial Waste [Economía Circular: Obtención y Encapsulación de Compuestos Polifenólicos Provenientes de Residuos Agroindustriales] - Gutierrez-Cutino, M; Gutierrez-Cutino, M; Matiacevich, S; Soto-Madrid, D (Institute of Advanced Studies, University of Santiago de Chile, 2023)
This work aims to resume the principles and strategies at a global and national level on the circular economy, as well as the possible raw materials of polyphenolic compounds from waste from the Chilean agroindustry, ending with the most used technique and wall material (drying spray using maltodextrin) for the encapsulation of these antioxidant compounds to generate potential natural additives, thus contributing to the circular economy. Nevertheless, waste in the Chilean agroindustry is not sufficiently exploited or studied to find significant added value, as is the case in other countries that have successful circular economy initiatives. © 2023 by the Author(s).